Structural Characterization of Arginine Fingers - Identification of an Arginine Finger for the Pyrophosphatase dUTPases - Nagy, Gergely Budapest University Of Technology; Lopata, Anna Hungarian Academy Of Sciences; Ozohanics, Olivér Hungarian Academy Of Sciences; Vékey, Károly Hungarian Academy Of Sciences; Brooks, Bernard R National Institutes Of Health; Leveles, Ibolya Budapest University Of Technology; Tóth, Judit Hungarian Academy Of Sciences; Vértessy, Beata G Budapest University Of Technology (King's College London, 2016)
This data contains classical MD trajectories and QM/MM reaction path geometries.
Keywords: MD simulations, QM/MM calculations